2011
DOI: 10.1016/j.jemermed.2011.06.099
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Two Freestanding Emergency Departments on a Tertiary Care Center

Abstract: States and Canada and whether opportunities exist to render care in a more cost-effective manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Initial data show that they may reduce ED crowding in neighboring hospitals while increasing the volume of emergency care delivered in a region. 7 Although questions remain on how best to implement freestanding EDs on a permanent basis, 6 such facilities may Rebuilding Emergency Care After Hurricane Sandy Disaster Medicine and Public Health Preparedness serve a unique, transitional role when inpatient care is compromised in disasters. Permanent freestanding EDs are constructed following a period of market analysis with established provider agreements, referral networks, and transfer arrangements.…”
Section: Discussion Freestanding Emergency Departmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial data show that they may reduce ED crowding in neighboring hospitals while increasing the volume of emergency care delivered in a region. 7 Although questions remain on how best to implement freestanding EDs on a permanent basis, 6 such facilities may Rebuilding Emergency Care After Hurricane Sandy Disaster Medicine and Public Health Preparedness serve a unique, transitional role when inpatient care is compromised in disasters. Permanent freestanding EDs are constructed following a period of market analysis with established provider agreements, referral networks, and transfer arrangements.…”
Section: Discussion Freestanding Emergency Departmentsmentioning
confidence: 99%
“…In areas with sufficient inpatient capacity, freestanding EDs have emerged as an alternative to traditional hospital-based EDs. Initial data show that they may reduce ED crowding in neighboring hospitals while increasing the volume of emergency care delivered in a region 7 …”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that hospitalbased ED volumes declined significantly when freestanding EDs opened within a twelve-mile radius, despite the fact that the overall ED volume in that particular health care system increased. 15 Theoretically, if freestanding EDs cause hospital-based EDs to have lower patient volumes, hospital-based EDs might have lower waiting times. However, our analysis showed that the entry of freestanding EDs did not significantly affect the waiting times of nearby hospital-based EDs.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…One study of a hospital ED at a tertiary care center found that patient volume fell 7.5% during a period of 3 years when two FrEDs opened nearby, while total patient volume for all three facilities combined rose 45% . Another study found that Medicare expenditures per beneficiary were $55 higher for each FrED that entered a county between 2003 and 2009.…”
Section: Discussionmentioning
confidence: 99%